Ultramicroporous carbons featuring sub‐Ångstrom tunable apertures for the selective separation of light hydrocarbon. Issue 9 (3rd May 2021) - Du, Shengjun; Wang, Xingjie; Huang, Jiawu; Kent, Kirlikovali; Huang, Baolin; Karam, Idrees; Li, Zhong; Xiao, Jing
Abstract: Separations of both C3 alkene/alkane and C4 alkadiene/alkenes are of great commercial significance as propylene and butadiene represent important feedstock chemicals, but the full extraction of them using carbon‐based separating agents has yet to be fully realized. Herein, derived from low‐cost starch precursors, we report a series of ultramicroporous starch‐based carbon materials (SC‐M; M = Na, K, Rb), with sub‐Ångstrom tunable ultramicropore apertures to separate the targeted gases with high purity. Among these materials, potassium derivative SC‐K can deliver high uptake capacities of propylene and butadiene (up to 2.20 and 2.36 mmol/g, respectively, at 100 kPa and 298 K) and superior selectivities due to a molecular‐sieving effect, as evidenced through adsorption isotherms and breakthrough experiments. Low heats of adsorption enable regeneration of SC‐M under mild conditions. To our knowledge, SC‐K represents the sole example of a porous carbon material that demonstrates potential for highly selective sieving‐driven separation of both C3 alkene/alkane and C4 alkadiene/alkenes.